2011
DOI: 10.1021/ja207388v
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene-Promoted versus Ethylene-Free Enyne Metathesis

Abstract: The role of ethylene in promoting metathesis of acetylenic enynes is probed within the context of ring-closing enyne metathesis, using first- and second-generation Grubbs catalysts. Under inert atmosphere, rapid catalyst deactivation is observed by calibrated GC-FID analysis for substrates with minimal propargylic bulk. MALDI-TOF mass spectra reveal a Ru(enyne)(2) derivative that exhibits very low reactivity toward both enyne and ethylene. Under ethylene, formation of this species is suppressed. Enynes with bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 40 publications
8
69
0
1
Order By: Relevance
“…For instance, alkynes can react exclusively with the initiator in a oligomerization reaction). 44,45 Early mechanistic studies of RCEYM suggested an 'alkylidene-first' reaction mechanism based on NMR studies. In RCM depicted in equation 8, Hoye recognized that there were two possibilities: reaction of [Ru]¼ CH 2 with the alkyne directly or initial transalkylidenation to generate an alkylidene 9 (Scheme 3).…”
Section: Mechanism Of Eymmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, alkynes can react exclusively with the initiator in a oligomerization reaction). 44,45 Early mechanistic studies of RCEYM suggested an 'alkylidene-first' reaction mechanism based on NMR studies. In RCM depicted in equation 8, Hoye recognized that there were two possibilities: reaction of [Ru]¼ CH 2 with the alkyne directly or initial transalkylidenation to generate an alkylidene 9 (Scheme 3).…”
Section: Mechanism Of Eymmentioning
confidence: 99%
“…55 Further insight into the ethylene effect has been provided by observations made using matrix-assisted laser desorption/ionization (MALDI) mass spectral analysis under inert atmosphere conditions. 44 Fogg and coworkers had developed mass spectral analysis as a tool for studying intermediates and decomposition products of ruthenium carbenes relevant to metathesis. The RCEYM of the malonate shown in Scheme 5 was considered in terms of both the ene-then-yne and the yne-then-ene pathway.…”
Section: Role Of Ethylene In Ring-closing Enyne Metathesis (Mori's Comentioning
confidence: 99%
See 3 more Smart Citations